Unveiling the size effect of Pt-on-Au nanostructures on CO and methanol electrooxidation by in situ electrochemical SERS. Issue 9 (24th February 2020) - Chen, Xing; Liang, Miao-Miao; Xu, Juan; Sun, Han-Lei; Wang, Chen; Wei, Jie; Zhang, Hua; Yang, Wei-Min; Yang, Zhi-Lin; Sun, Jian-Jun; Tian, Zhong-Qun; Li, Jian-Feng
Abstract : Size effects of Pt on electrooxidation are revealed by in situ electrochemical SERS using bifunctional Au–Pt core–satellite nanocomposites. Abstract : In situ monitoring of electrocatalytic processes at solid–liquid interfaces is essential for the fundamental understanding of reaction mechanisms, yet quite challenging. Herein, Pt-on-Au nanocatalysts with a Au-core Pt-satellite superstructure have been fabricated. In such Pt-on-Au nanocatalysts, the Au cores can greatly amplify the Raman signals of the species adsorbed on Pt, allowing the in situ surface-enhanced Raman spectroscopy (SERS) study of the electrocatalytic reactions on Pt. Using the combination of an electrochemical method and in situ SERS, size effects of Pt on the catalytic performance of the core–satellite nanocomposites towards CO and methanol electrooxidation are revealed. It is found that such Pt-on-Au nanocomposites show improved activity and long-term stability for the electrooxidation of CO and methanol with a decrease in the Pt size. This work demonstrates an effective strategy to achieve the in situ monitoring of electrocatalytic processes and to simultaneously boost their catalytic performance towards electrooxidation.